Service life prediction of corrosion-affected reinforced concrete columns based on time-dependent reliability analysis. (November 2020) - Firouzi, Afshin; Abdolhosseini, Mohaddeseh; Ayazian, Rouhollah
Highlights: Reliability of corrosion affected reinforced concrete columns is assessed. Corrosion affects tensile region of the column interaction curve more significantly. Loss of confinement and spalling of concrete due to corrosion is modelled. Abstract: Reinforced concrete columns in chloride-laden environments are prone to steel reinforcement corrosion, which reduces their capacity to resist applied loads. The current study modeled the time-dependent effect of corrosion as a non-stationary Gaussian process while accounting for the uncertainties of other parameters using random variables. The down-crossing rate of the residual capacity of these structures under combined axial loads and bending moments from the safe domain has been calculated using a recently derived closed-form equation, and the corresponding first passage probability has been estimated over the service life of the column. It was found that corrosion significantly affected the remaining service life of the columns due to the loss of reinforcement, especially in the tensile region of the column interaction curve. This indicates that the probability of failure due to lateral loads and bending moments in corrosion-affected columns can be significantly high; therefore, the load and resistance factors in design codes and standards should be calibrated accordingly. It is also found that if the effects of confinement loss of core concrete of column and spalling of concrete cover due to corrosion of transverse reinforcement are modeled as well the reliability index profiles in tensile and compressive regions of the interaction curve would match more closely. This is a research domain which needs further investigations.